Design and Development of a Microcontroller-Based Water Usage Monitoring and Control System - Aulia Muhandas Prawoto; Yerry Febrian Sabanise (Indonesian Journal of Electronics and Computer Technology, 2026)
Water is one of the fundamental human necessities that plays a crucial role in supporting daily domestic activities. However, uncontrolled water consumption frequently results in excessive usage and increased household water expenditure. This study aims to design and implement a microcontroller-based water usage monitoring and control system to improve water-use efficiency and facilitate real-time monitoring. The proposed system utilizes the Wemos D1 R1 as the primary microcontroller integrated with a water flow sensor to detect water discharge, a water level sensor to monitor water levels in the storage tank, relays, a water pump, a solenoid valve, an LCD 20x4 display, and Firebase database integration for Android-based data communication and monitoring. The research methodology consists of analysis, design, testing, implementation, and maintenance stages. The implementation results demonstrate that the system is capable of monitoring water usage discharge, displaying water level information, and performing automatic control of the water filling process in the storage tank. The developed system is expected to improve household water-use efficiency and assist users in controlling water consumption more effectively and systematically.